Assessment of a Single Intra-Articular Stifle Injection of Pure Platelet Rich Plasma on Symmetry Indices in Dogs with Unilateral or Bilateral Stifle Osteoarthritis from Long-Term Medically Managed Cranial Cruciate Ligament Disease - Venator KP (Dove Medical Press, 2020)
Kurt P Venator,* Christopher W Frye,* Lauri-Jo Gamble, Joseph J Wakshlag Department of Clinical Sciences, Cornell University College of Veterinary Medicine, Ithaca, NY 14853, USA*These authors contributed equally to this workCorrespondence: Joseph J WakshlagCornell University College of Veterinary Medicine, Vet. Med. Center C2-008, Ithaca, NY 14853, USATel +1 607 351 6545Email dr.joesh@gmail.comPurpose: The use of platelet-rich plasma (PRP) to treat canine osteoarthritis has gained support within the scientific community. PRP effects on pain control for degenerative joint disease induced by naturally occurring cranial cruciate ligament instability are limited, particularly in a cohort of dogs with chronic instability and osteoarthritis (> 12 months), representing a commonly encountered clinical population that often defaults to medical management. The goal of this study was to assess the effects of a single intra-articular PRP injection into an effected stifle in this cohort, to assess response to treatment, quantitative kinetic data as it relates to percent body weight for peak vertical force (PVF) and vertical impulse (VI) were collected, and symmetry indices related to PVF were determined.Methods: Twelve dogs with unilateral or bilateral osteoarthritis with ruptured, non-stabilized cranial cruciate ligaments over 12 months duration were identified. Unilateral injections of 2.5 mL of a PRP preparation into the most severely affected stifle based on kinetic analysis was performed. Repeat pressure-sensitive walkway analysis was conducted monthly for 3 months. Peak vertical force (PVF) and vertical impulse (VI) were normalized to body weight and identified in all four limbs. Previously published symmetry indices regarding PVF were calculated, comparing the treated limb with the contralateral limb, ipsilateral forelimb, and contralateral forelimb.Results: After treatment, hind limb symmetry index (SI) regarding PVF showed improved symmetry, suggesting more weight placement at all-time points after injection of the most affected limb (p < 0.01). Further, PVF asymmetry indices assessing contralateral fore (CFL) and hind limb (CHL) as well as ipsilateral forelimb (IFL) revealing a significant decrease from baseline for CHL at week 4 (p = 0.02), but not weeks 8 and 12. The CFL showed decreased differences in symmetry from baseline at each time point (p = 0.03). There were no statistically significant changes in PVF or VI over time in treated dogs.Conclusion: A single injection of PRP improved kinetics for minimally 4 weeks with some data suggesting an effect for up to 12 weeks. Therefore, PRP might be a viable therapeutic option for instability and inflammation associated with chronic osteoarthritis due to cranial cruciate ligament disease in the non-surgical patient.Keywords: platelet, stifle, canine, osteoarthritis and cruciate